Zur Geometrie der Normalsysteme von einfachen Differentialgleichungen höherer Ordnung - Bliznikas, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Близникас. О геометрии нормальных систем обыкновенных дифференциальных уравнений высшего порядка V. Bliznikas. Aukštesnės eilės paprastų diferencialinių lygčių normalinių sistemų geometrijos klausimu